Limits in the use of cPTIO as nitric oxide scavenger and EPR probe in plant cells and seedlings - D'Alessandro, Stefano; Posocco, Bianca; Costa, Alex; Zahariou, Georgia; Lo Schiavo, Fiorella; Carbonera, Donatella; Zottini, Michela (Frontiers in Plant Science, 2013)
Over the last decade the importance of nitric oxide (NO) in plant signaling has emerged. Despite its recognized biological role, the sensitivity and effectiveness of the methods used for measuring NO concentration in plants are still under discussion. Among these, electron paramagnetic resonance (EPR) is a well-accepted technique to detect NO. In the present work we report the constraints of using 2-4-carboxyphenyl-4,4,5,5-tetramethylimidazoline-1-oxyl-3-oxide (cPTIO) in biological samples as spin trap for quantitative measurement of NO. EPR analyses on Arabidopsis cell cultures and seedlings show that cPTIO(NNO) is degraded in a matter of few minutes while the (INO) compound, produced by cPTIO and NO reaction, has not been detected. Limitations of using this spin trap in plant systems for quantitative measurements of NO are discussed. As NO scavenger, cPTIO is widely used in combination with 4-amino-5-methylamino-2',7'-difluorofluorescein (DAF) fluorescent dye in plant research. However, the dependence of DAF fluorescence on cPTIO and NO concentrations is not clearly defined so that the range of concentrations should be tightly selected. In this context, a systematic study on cPTIO NO-scavenging properties has been performed, as it was still lacking for plant system applications. The results of this systematic analysis are discussed in terms of reliability of the use of cPTIO in the quantitative determination and scavenging of NO in plants and plant cultured cells.